CONTROL OF THE PROCESS OF SCORCHING BY MEANS OF ITS MICROALLOYING AT CONTINUOUS CASTING. Message 2. Generalization of experimental results - Ju. A. Samojlovich; V. I. Timoshpolskij; I. A. Trusova; A. A. Matochkin (Литьë и металлургия)
The available experimental data are generalized with the purpose of determination of relation between speed of dendrite crystals growth and size of diffusion overcooling for different grades of steel.